Energy Evolution Characteristics of Rock Under Different Confining Conditions - Zhang, Bi-Wen; Fang, Kai; Wang, Chen; Zhao, Tong-Bin; Zhang, Xiu-Feng (Frontiers in Earth Science, 2022)
Constant stiffness confining condition seems more reasonable than constant stress confining condition to simulate the actual confining stress environment of in situ rock which varies with the lateral strain. Compression tests of sandstone samples with two different confining conditions were conducted to study the energy evolution characteristics of rock under constant stress confining condition and constant stiffness confining condition. Except for the conventional triaxial compression tests, CFRP-confined rock samples were also used to simulate the constant stiffness confinement of the rock specimen in the laboratory. The stress–strain curve and failure mode of the samples under different confining conditions were compared. The influence of confining condition on the characteristics of rock energy evolution was investigated. The results show that the stress–strain curves under the confining conditions of constant stress and constant stiffness exhibited strain softening and strain hardening, respectively. Under constant stress confining condition, the specimen failed in the ductile mode while the specimen exhibited a sudden and brittle failure behavior under constant stiffness confining condition. The evolution trend of the elastic strain energy was greatly affected by the magnitude of confining stiffness. The elastic strain energy of the specimen under low stiffness confining condition decreased slightly after reaching its peak. As the confining stiffness increased, the elastic strain energy would not decrease but continued to increase until the failure of the specimen. The maximum elastic strain energy under the confining condition of the high confining stiffness is greater than that of constant stress. Considering the influence of confining stiffness on the storage and release of the strain energy, to obtain the true mechanical behavior of the rock mass under confining conditions, stiffness confining conditions should be taken into consideration in the laboratory.